Automating Induction with an SMT Solver - Leino, Rustan (2011)
Mechanical proof assistants have always had support for inductive proofs. Sometimes an alternative to proof assistants, satisfiability modulo theories (SMT) solvers bring the hope of a higher degree of automation. However, SMT solvers do not natively support induction, so inductive proofs require some encoding into the SMT solver’s input. This paper shows a surprisingly simple tactic—a rewriting strategy and a heuristic for when to apply it—that has shown to be useful in verifying simple inductive theorems, like those that can occur during program verification. The paper describes the tactic and its implementation in a program verifier, and reports on the positive experience with using the tactic.